“Women Will Never Be Equal to Men”: Examining Women Journalists’ Experiences of Patriarchy and Sexism in South Africa - Genevieve Govender; Tigere P. Muringa (Journalism and Media)
Research shows that gender transformation policies and programmes within the media industry have done little to curtail sexism and patriarchal values in news reporting. This study’s term ‘patriarchy’ refers to the systemic structures of masculine dominance entrenched in societal, cultural, and institutional norms. This systemic understanding is complemented by exploring individual acts that perpetuate sexism, understood as both explicit and implicit forms of discrimination based on gender. Within newsrooms, where considerable studies have been conducted, data show alarming evidence of extensive sexism and patriarchal values, which are often nuanced and embedded into daily operations. Significantly, the current body of research argues that the problems experienced within the newsroom manifest a societal issue. However, there is a need for more research that turns the spotlight specifically on how newsmakers interact with women reporters in the field. This paper investigates how sexism and gender-based power imbalances affect female journalists’ professional experiences and roles in South Africa. The paper uses qualitative methods to explore how gender inequality and male dominance influence female journalists’ roles, opportunities, and treatment within the profession. This paper contributes to the current discourse by arguing that deeply ingrained societal and cultural patriarchal norms significantly shape and restrict the professional lives of women reporters. Data were collected using semi-structured interviews with eleven (n = 11) reporters drawn from various SABC radio reporters across the nine provinces in South Africa. The study’s findings detailed multiple layers of discrimination and harassment experienced by reporters when engaging with newsmakers. Evidenced in the research is how entrenched societal and cultural values limit and influence the productivity of the reporters and impede their freedom to tell stories effectively. Besides the documented glass ceilings that stunt the upward progression of female reporters, the study posits the existence of invisible walls that hinder their transversal advancement within their designated scope of reporting.